METHODS OF TEACHING MATHEMATICAL MODELING TO STUDENTS OF THE PEDAGOGICAL INSTITUTES - Bissembayev К.; Boranbekova А.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The purpose of this article is to reveal a number of modern problems and methods for the implementation of professional oriented training of students of the specialty physics using mathematical modeling. Future physics teachers are offered methods of applying mathematical modeling in teaching activities. It also describes a specific method of preparing students to use mathematical modeling in solving physical problems. In recent years, mathematical modeling has become a separate branch of knowledge that has methods for studying its own objects. Therefore, the study of mathematical modeling, the ability to use it in the study of physical and mechanical processes and the training of schoolchildren and students is one of the important problems. Using a mathematical model, students learn the mathematical apparatus for describing objects, physical phenomena, or the real world.